PERAN GRUP WHATSAPP KELAS DALAM INTERAKSI SOSIAL DAN KOMUNIKASI MAHASISWA PROGRAM STUDI ADMINISTRASI PENDIDIKAN ANGKATAN 2022 - gita puspita (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This research aims to explore the role of WhatsApp groups in social interaction and communication of Administration Study Program students Class of 2022 education. With the development of communication technology, Instant messaging applications such as WhatsApp have become an important tool for students to communicate and coordinate in the environment academic. WhatsApp groups function not only as a medium dissemination of lecture information but also as a platform for supports social interaction outside formal lectures and facilities long distance communication. This research uses a qualitative approach with data collection techniques in the form of observation, interviews structured, and documentation. The results showed that group WhatsApp plays a vital role in conveying information important matters, discussing lecture material, arranging meetings, as well as strengthening social relationships and building learning communities who is supportive. However, there are several challenges such as network limitations and quotas, as well as potential miscommunications are also identified.